2022
DOI: 10.3390/molecules27165055
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile, Bioactivities, and Safety of Turmeric Oil

Abstract: The pharmacological attributes of turmeric have been extensively described and frequently related to the action of curcuminoids. However, there is also scientific evidence of the contribution of turmeric oil. Since the oil does not contain curcuminoids in its composition, it is crucial to better understand the therapeutic role of other constituents in turmeric. The present review discusses the pharmacokinetics of turmeric oil, pointing to the potential application of its active molecules as therapeutic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Based on these results, it can be concluded that TEO contains phenolic and terpenoid compounds. Several studies reported that TEO has powerful antioxidant potential both in-vitro and in-vivo [2,8,31]. Oxygenated monoterpenes and sesquiterpenes, such as ar-turmerone, α-turmerone, and βturmerone, were included in the terpenoid compounds and reported to play a role in this activity.…”
Section: Identification Of Teomentioning
confidence: 99%
“…Based on these results, it can be concluded that TEO contains phenolic and terpenoid compounds. Several studies reported that TEO has powerful antioxidant potential both in-vitro and in-vivo [2,8,31]. Oxygenated monoterpenes and sesquiterpenes, such as ar-turmerone, α-turmerone, and βturmerone, were included in the terpenoid compounds and reported to play a role in this activity.…”
Section: Identification Of Teomentioning
confidence: 99%
“…Orellana-Paucar et al presented another interesting review about turmeric oil [ 17 ]. The aims of this review were to discuss its pharmacokinetics, pointing to a potential application of its active molecules in therapy.…”
Section: Contributionsmentioning
confidence: 99%
“…The constituents of the leaf, rhizome, and flowers of C. longa have been extensively studied [ 21 , 22 , 23 ]. The rhizome essential oil has been reported to exhibit antimicrobial, anti-cancer, insecticidal, larvicidal, repellent, and antioxidant activities [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%